COMPARISON OF GRAMMAR TRANSLATION METHOD AND ECLECTIC METHOD IN ENHANCING STUDENTSâ VOCABULARY ACHIEVEMENT - Katemba, Caroline V.; Hulu, Grace; Panjaitan, Nelson B. (Journal of Language Pedagogy, 2011)
ABSTRACT: In teaching language there are some factors that should be considered in order to make the teaching learning process work and reach the success. The teacher should know how to make the language teaching effective, who the learners are, the method and technique that is suitable with the need of the learners and the condition of the classroom. Due to the reason above, this study entitled âComparison of Grammar Translation method and Eclectic Method in Enhancing Students Vocabulary Achievementâ was employed to investigate and examine their difference in teaching vocabulary to the early students. The participants involved in this study were grade 4 students of Karyawangi Elementary School Parongpong Bandung. This study has three major activities that were involved. They were: Pretest, implementation of Grammar Translation method and Eclectic Method and post test. The participants were commanded to answer the multiple choice test in pre test and post test. During the implementation, the participants were taught vocabulary by using the different method for each group. This research obtained data follows: n1=27, n2=33, Î±=0.05, mean difference of Grammar Translation Method was 19.22 where mean difference for the Eclectic group was 22.29. After the treatment it was obtained that the mean of post test of Grammar group were 57.14 and for the Eclectic group the mean of post test were 60.21. From mean of gain of the post test result (The result show that tobserved > ttable: 2.9 > 1.645), it can be concluded that the mean of gain of Eclectic group is higher than the mean of Grammar Translation Method studentsâ vocabulary achievement and Eclectic method studentsâ vocabulary achievement.